CLASS/HI-CLASS como uma ferramenta de trabalho e ensino de cosmologia e programação - Fontana, Cristiane (Cadernos de Astronomia, 2024)
Summary of the poster presented in the second edition of the As Astrocientistas event, held between 7 and 10 February 2023.